Explaining the size of the mutual fund industry around the world - KHORANA, A; SERVAES, H; TUFANO, P (Journal of Financial Economics, 2005)
This paper studies the mutual fund industry in 56 countries and examines where this financial innovation has flourished. The fund industry is larger in countries with stronger rules, laws, and regulations, and specifically where mutual fund investors’ rights are better protected. The industry is also larger in countries with wealthier and more educated populations, where the industry is older, trading costs are lower and in which defined contribution pension plans are more prevalent. The industry is smaller in countries where barriers to entry are higher. These results indicate that laws and regulations, supply-side and demand-side factors simultaneously affect the size of the fund industry.